Op Amp applications handbook - Jung, Walter G. (Burlington, MA : Newnes, 2006)
Operational amplifiers play a vital role in modern electronics design. The latest op amps have powerful new features, making them more suitable for use in many products requiring weak signal amplification, such as medical devices, communications technology, optical networks, and sensor interfacing. The Op Amp Applications Handbook may well be the ultimate op amp reference book available. This book is brimming with up-to-date application circuits, valuable design tips, and in-depth coverage of the latest techniques to simplify op amp circuit designs, and improve their performance. As an added bonus, a selection on the history of op amp development provides an extensive and expertly researched overview, of interest to anyone involved in this important area of electronics. * Seven major sections packed with technical information * Anything an engineer will want to know about designing with op amps can be found in this book * Op Amp Applications Handbook is a practical reference for a challenging engineering field.
Foreword -- Preface -- Acknowledgments -- Op Amp History Highlights -- Chapter 1: Op Amp Basics -- Chapter 2: Specialty Amplifiers -- Chapter 3: Using Op Amps with Data Converters -- Chapter 4: Sensor Signal Conditioning -- Chapter 5: Analog Filters -- Chapter 6: Signal Amplifiers -- Chapter 7: Hardware and Housekeeping Techniques -- Chapter 8: Op Amp History -- Index.
"First Elsevier printing November, 2004"--T.p. verso.
Includes bibliographical references and index.
Keywords: Operational amplifiers -- Handbooks, manuals, etc; Electronic books